IgA vasculitis nephritis (Schönlein-Henoch purpura with nephritis) following COVID-19 vaccination - Leila Mahmoodnia; Shahin Asgari Savadjani; Leila Mostafavi; Setayesh Sotoudehnia Korani; Fatemeh Mohammad Alizadeh; Mahshid Sadat Chenarani Moghadam; Hamid Reza Jahantigh; Sina Neshat; Ali Shirbacheh; Jyoti Baharani; Rohollah Masomi; Zahra Golestani Hotkani (Society of Diabetic Nephropathy Prevention, 2023)
IgA vasculitis nephritis (Schönlein-Henoch purpura nephritis) is an autoimmune circumstance characterized by palpable purpura involving the lower limbs, arthralgia, abdominal pain and kidney involvement. It is possible that a cytokine storm following coronavirus disease 2019 (COVID-19) could lead to an immunological dysregulation responsible for IgA vasculitis nephritis in these cases. Reactivation or first onset of IgA vasculitis nephritis is uncommon; however, there have been increasing reports of this disease, as a complication of COVID-19 vaccination. It is possible that COVID-19 mRNA vaccination may trigger several auto-inflammatory and autoimmune cascades. Previous research has shown that Toll-like receptors play a role in the development of IgA vasculitis nephritis. Following injection of a COVID-19 mRNA vaccine, the uptake of double-stranded RNA by-products will trigger Toll-like receptors, leading to a series of intracellular cascades starting an innate immunity-driven process of cell-mediated and humoral- mediated immunity.